2015
DOI: 10.1007/s00228-015-1960-6
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma pharmacokinetics and synovial concentrations of S-flurbiprofen plaster in humans

Abstract: PurposeThe purpose of this study is to investigate the pharmacokinetics and deep tissue penetration capability of the newly developed S-flurbiprofen plaster (SFPP) in humans.MethodsStudy 1: SFPP tape-type patch (2–60 mg) was applied to the lower back for 24 h in healthy adult volunteers. S-flurbiprofen (SFP) plasma concentration was measured over time to examine SFP pharmacokinetics.Study 2: SFPP (20 mg) was applied for 12 h to the affected knee of osteoarthritis (OA) patients who were scheduled for total knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 18 publications
(17 reference statements)
1
33
0
Order By: Relevance
“…We also showed that SFP was a 1000‐fold more potent than RFP at inhibiting PGE 2 production from peritoneal leukocytes stimulated with bacterial suspensions (IC 50 = 14 n m for SFP and 17 000 n m for RFP, respectively) Furthermore, we demonstrated that the skin permeability of SFP, the active ingredient of SFPP, was superior to that of ketoprofen or loxoprofen contained in the respective patches in Healthy SD rats, and also that application of SFPP was associated with the most potent analgesic efficacy and inhibitory effect on PGE 2 production in the AIA model among the three patches compared . Based on a clinical study, we reported that in knee OA patients, a higher drug penetration into the synovial tissues was observed for SFPP as compared to the FP patch . PGE 2 production is increased in the synovial fluid of OA patients .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We also showed that SFP was a 1000‐fold more potent than RFP at inhibiting PGE 2 production from peritoneal leukocytes stimulated with bacterial suspensions (IC 50 = 14 n m for SFP and 17 000 n m for RFP, respectively) Furthermore, we demonstrated that the skin permeability of SFP, the active ingredient of SFPP, was superior to that of ketoprofen or loxoprofen contained in the respective patches in Healthy SD rats, and also that application of SFPP was associated with the most potent analgesic efficacy and inhibitory effect on PGE 2 production in the AIA model among the three patches compared . Based on a clinical study, we reported that in knee OA patients, a higher drug penetration into the synovial tissues was observed for SFPP as compared to the FP patch . PGE 2 production is increased in the synovial fluid of OA patients .…”
Section: Discussionmentioning
confidence: 58%
“…We previously demonstrated the superior skin permeability of SFP as compared to that of FP in the yucatan micropig (YMP) model in vitro . Another clinical study demonstrated superior percutaneous absorption and greater tissue penetration of the active ingredient of SFPP as compared to that of an FP patch . We demonstrated in a previous study that topical application of SFPP produced an immediate and strong analgesic effect in a rat model of adjuvant‐induced arthritis (AIA) .…”
Section: Introductionmentioning
confidence: 99%
“…Although topical NSAIDs have a lower risk of gastrointestinal disorder compared with oral NSAIDs,6 the use of SFPP might increase the risk due to its high percutaneous absorption and systemic exposure 19. Nevertheless, the study results demonstrated low incidence of gastrointestinal disorder in SFPP groups (0%, 0.8%, and 0.7% in SFPP 10, 20, and 40 mg, respectively), indicating that SFPP had a similarly low risk as that of existing topical NSAIDs.…”
Section: Discussionmentioning
confidence: 69%
“…In a study conducted in healthy adult males, SFPP provided sustained and stable plasma levels of S-flurbiprofen 19. Furthermore, a study in knee OA patients demonstrated higher synovial transfer of S-flurbiprofen compared with that of an existing flurbiprofen patch formulation 19.…”
Section: Introductionmentioning
confidence: 99%
“…We showed in an experimental study using rats that the NSAID patch developed by us, the S-flurbiprofen plaster (SFPP), containing an (S)-enantiomer of flurbiprofen, was demonstrated to rapidly suppress inflammatory pain in the rat AIA model and also to show superior absorbability as compared to ketoprofen and loxoprofen patches [6]. Furthermore, we reported that the superior percutaneous absorption and greater tissue penetration of SFP into the human synovial tissue following application of SFPP in knee osteoarthritis (OA) patients [7].…”
Section: Introductionmentioning
confidence: 99%